Analisis Kelayakan Bisnis dan Strategi Operasional Start-Up Fashion Travel-Wear: Studi Kasus TRAVRL - Aziz Muhammad Rizqi; Hani Humaeriyah (INDO PUBLISHING, 2026)
This study aims to conduct an in-depth evaluation and comprehensive analysis of the business feasibility study of the fashion start-up